2017
DOI: 10.1007/s11248-017-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs

Abstract: Producing aflatoxin-detoxifizyme (ADTZ) in pigs to control the AFT contamination of pig feed is a new research strategy by transgenic technology. In this study, transgenic pigs specifically expressing ADTZ gene in the parotid gland were successfully produced by somatic cell nuclear transfer technology. The ADTZ activity in saliva of 6 transgenic pigs was found to be 7.11 ± 2.63 U/mL. The feeding trial with aflatoxin (AFT) results showed that there were significant difference about the serum biochemical index s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, as noted by Segard et al (42), autocrine/paracrine GH has been linked to muscle cell proliferation and myotube differentiation. This concept elucidates the observed increase in pectoral muscle fiber density in this experiment, which can be attributed to the elevated expression and Research indicated that increased TP and albumin levels, along with enhanced activities of AST, ALT and AKP, were markers of high protein metabolism in the body (43,44). Conversely, BUN levels had been found to inversely correlate with protein synthesis (45).…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, as noted by Segard et al (42), autocrine/paracrine GH has been linked to muscle cell proliferation and myotube differentiation. This concept elucidates the observed increase in pectoral muscle fiber density in this experiment, which can be attributed to the elevated expression and Research indicated that increased TP and albumin levels, along with enhanced activities of AST, ALT and AKP, were markers of high protein metabolism in the body (43,44). Conversely, BUN levels had been found to inversely correlate with protein synthesis (45).…”
Section: Discussionsupporting
confidence: 67%
“…Various physical, chemical, and biological approaches to preventing AFB 1 contamination have been developed [ 13 , 14 , 15 ]. For instance, transgenic pigs expressing aflatoxin-detoxifizyme (ADTZ) exhibit resistance to AFB 1 toxicity [ 16 ]. Nevertheless, economic losses and threats to public health caused by AFB 1 contamination persist [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, feedstuffs may also contain toxic factors such as mycotoxins. To combat these fungal toxins, a bacterial gene that encodes and enzyme that detoxifies aflatoxin was expressed in the salivary gland of first the mouse (Guan et al 2015 ) and then the pig (Lou et al 2017 ). Unlike the experiments above that measured digestive parameters, these experiments required an examination of the impact of aflatoxin on the liver.…”
Section: Digestion Improvement With Genetically Engineered Pigsmentioning
confidence: 99%